Seroprevalence and Genotypic Distribution Patterns of Hepatitis C Virus among Infected Patients from Sulaimaniyah Province: Iraq - Hasan, Awat Jamal; Ramzi, Zhian Salah; Alshekhani, Mohammed Abdulrahman (Sulaimani Journal for Pure and Applied Sciences, 2023)
Background: The hepatitis C virus (HCV) is a prevalent cause of liver illness. The virus displays a high degree of genetic variability, with documented geographical differences in genotype predominance. Objective: This study aimed to determine the prevalence of HCV genotypes among people who lived in Sulaimaniyah province, Kurdistan region of Iraq. Patients and Methods: Blood samples were collected from 229 individuals identified as having a confirmed positive HCV antibody and who had been referred to the Public Health Laboratory in Sulaimaniyah city by medical professionals for genotyping from July 2021 to December 2022. Following the extraction of the viral RNA, a PCR-based genotyping kit was used to identify the HCV genotype. Results: The most prevalent genotype was GT1a (31.6%), followed by GT1 and GT4 (23.6%) and then GT1b (7.9%). Mixed genotypes were observed in 10.4% of samples. Males were affected mainly by HCV (58.5%) than females (41.5%). The frequency of GT1a was higher in males (32.1%) compared to females (30.5%). On the other hand, males exhibited a more excellent distribution of GT4 and GT1 than females, while GT1b and GT5 were observed more in females than males. Among mixed genotypes, GT5 or 6 was the most prevalent infection type (no.=8, 3.5%), while GT1a, 3 reported the lowest rate (no.=1, 0.4%). Conclusion: This study assesses the HCV genotype distribution among infected HCV patients in Sulaimaniyah, which is distinct from the prevalent distribution in Iraq and Middle Eastern Arab nations, but it is equivalent to the distribution worldwide.
Keywords: HCV Genotyping; seroprevalence; Liver disease; cross sectional study